Energy Efficiency and Thermal Comfort in Hospital Buildings: A Review - Gatea, Anwer; Mohideen Batcha, Mohd Faizal; Taweekun, Juntakan (International Journal of Integrated Engineering, 2020)
This paper aims to review the state of the art technologies for the energy efficiency within the hospitals sector. Hospitals are liable for an unstable amount of energy demand and joint emissions, because of their 24/7 nature of operation and hence resulting larger energy consumption than a typical commercial building. Additionally, they need high quality and warranted supplies of electricity. Due to increased energy demand and therefore the depletion of existing fossil fuel based sources, it is required to use the energy more efï¬cient. Researchers found that hospitals represent close to 6% of total energy consumption within the utility buildings sector. Heating, Ventilation and air-con (HVAC) systems are the most important a part of electricity consumption at hospitals. Apart from effective energy management system, hospitals also require energy efficiency efforts and also incorporation with renewable energy if itâ€™s economically feasible. Apart from that, it is necessary to correlate the thermal comfort in hospitals to ensure the well-being of patients as well as optimum productivity of hospital workers. This paper reviews the energy efficiency efforts and their relation to thermal comfort in hospital buildings, to seek further research gaps for further works in this area.